Hedged out inequality and insecurity on Wall Street - Neely, Megan Tobias (University of California Press, 2022)
"Who do you think of when you imagine a hedge fund manager? A greedy fraudster, a visionary entrepreneur, a wolf of Wall Street? These tropes capture the public imagination of a successful hedge fund manager. But behind the designer suits, helicopter commutes, and illicit pursuits are the everyday stories of people who work in the hedge fund industry--many of whom don't realize they fall within the '1 percent' that drives the divide between the richest and the rest. With Hedged Out, sociologist and former hedge fund analyst Megan Tobias Neely gives readers an outsider's insider perspective on Wall Street and its enduring culture of inequality. Hedged Out dives into the upper echelons of Wall Street, where elite White masculinity is the standard measure for the capacity to manage risk and insecurity. Facing an unpredictable and risky stock market, hedge fund workers protect their interests by working long hours and building tight-knit networks with people who look and behave like them. Using ethnographic vignettes and her own industry experience, Neely showcases the voices of managers and other workers to illustrate how this industry of politically mobilized elites excludes people on the basis of race, class, and gender. Neely shows how this system of elite power and privilege not only sustains itself but builds over time as the beneficiaries concentrate their resources. Hedged Out explains why the hedge fund industry generates extreme wealth, why mostly White men benefit, and why reforming Wall Street will create a more equal society"--